A patient with human coronavirus NL63 falsely diagnosed with COVID-19; Lesson learned for the importance of definitive diagnosis. Issue 7 (July 2021) - Otsuka, Yuki; Hagiya, Hideharu; Nakano, Yasuhiro; Omura, Daisuke; Hasegawa, Kou; Yamada, Haruto; Iio, Koji; Honda, Tomoyuki; Otsuka, Fumio
Abstract: The gold standard for the diagnosis of coronavirus disease 2019 (COVID-19) is a nucleic acid detection test for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which may occasionally reveal false-positive or false-negative results. Herein, we describe a case of a patient infected with human coronavirus NL63 (HCoV-NL63) who was falsely diagnosed with COVID-19 using the Ampdirect™ 2019-nCoV detection kit (Shimadzu Corporation, Japan) and SARS-CoV-2 Detection Kit (TOYOBO co., ltd.), and was admitted to a COVID-19 hospital ward. We suspected a cross-reaction between HCoV-NL63 and SARS-CoV-2; however, the reported genome sequences of HCoV-NL63 and N1/N2 primers for SARS-CoV-2 do not correspond. Thus, the PCR result was supposed to be a false positive possibly due to contamination or human error. Although the issue of a false-negative result has been the focus of much attention to prevent the spread of the disease, a false positive is fraught with problems as well. Physicians should recognize that unnecessary isolation violates human rights and a careful diagnosis is indispensable when the results of laboratory testing for COVID-19 are unclear. Generally, in cases such as a duplicate PCR test was partially positive, either N1 or N2 alone was positive, PCR testing for two or more target regions resulted in a positive only for single region, a high cycle threshold >35 was obtained, a false positive should be suspected. Especially, when these conditions coincide, we should recognize the high likelihood of a false positive.